MOTIVES SELFIE AMONG THE STUDENT (Phenomenology Study in Instagram Group UNP Cantik) - Rizal Ikhsan (Sosioglobal, 2018)
This research is motivated by the interest of researcher in observing selfie phenomenon which has spread in every layer of society without exception to UNP is students who joined Instagram group of UNP Cantik (GUC). Researcher found that what they show in the GUC not only selfie, but also different expressions and background that they depict to the public. Obviously behind these actions, regardless of their motive that to show selfie photos with various forms of expression and background they want to perform. This study aims to analyze the motive of GUC’s student member. This study analyzed with theory of phenomenology by Alfred Schutz. This research was conducted with a qualitative approach with the type of phenomenology study research. The research result found that there were three Selfie motives of  GUC’s Members: (1) gainging the self-satisfaction and entertainment. (2) Building self image. (3) Drawing the attention of others